KNOWLEDGE, PERCEPTION, INCIDENCE OF INSECT PESTS AND OTHER AGRICULTURAL PRACTICES AMONG FARMERS GROWING VEGETABLESTHE COIMBATORE REGION, INDIA - PUSHPARAJ KARTHIKA; NATRAJ KRISHNAVENI (International Journal of Pharma and Bio Sciences, 2016)
Knowledge and perceptions of pests, diseases and pest management practices in major vegetables were investigated by interviewing 111 farmers in four localities in Coimbatore region. Most of the farmers considered arthropod pest problems as the major constraint to vegetable production. Various socio-demographic factors such as age, literacy, agricultural background were assessed. Maximum male farmers were middle aged while the female was 41-50 years. Literacy level was appreciable with 47.96% of the farmers underwent primary education. Agricultural and pest management practices including irrigation schemes, cropping patterns and utilization of pesticides were studied. Further, the critical infectious stages of the pests in various crops were analysed. Among the crops assessed, Brinjal was the highest pesticide requirement crop and the Hadda beetle, H. vigintiopunctata was the most serious pest affecting the crop.